Prevention of Cyclophosphamide-Induced Immunosuppression in Mice with the Antimicrobial Peptide Sublancin - Shuai Wang; Shuo Huang; Qianhong Ye; Xiangfang Zeng; Haitao Yu; Desheng Qi; Shiyan Qiao (Journal of Immunology Research)
Sublancin is a glycosylated antimicrobial peptide produced by Bacillus subtilis 168 with combined antibacterial and immunomodulatory activities. The purpose of this study was to evaluate the protective effects of sublancin on immunosuppression in cyclophosphamide-treated mice. In normal mice, the phagocytic activity of mouse peritoneal macrophages was significantly enhanced by oral administration of sublancin (1.0 mg/kg body weight) to BALB/c mice for 7 days (P<0.01). In addition, the mRNA expression of IL-1β, IL-6, and TNF-α in peritoneal macrophages from sublancin- (1.0 mg/kg body weight) administered mice was significantly increased (P<0.05). In cyclophosphamide-treated mice, oral sublancin administration accelerated the recovery of peripheral white blood cells, red blood cells, hemoglobins, and platelets and enhanced the macrophage phagocytic activity. Furthermore, sublancin restored the mRNA levels of IL-2, IL-4, and IL-6 in the spleen. Finally, the intestinal absorption of sublancin was poor as detected in the Caco-2 transwell system. Taken together, these findings suggest that sublancin plays a crucial role in the protection against immunosuppression in cyclophosphamide-treated mice and could be a potential candidate for use in immune therapy regimens.